2019
DOI: 10.3892/mmr.2019.10521
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of circRNA_089763 in the plasma exosomes of patients with post‑operative cognitive dysfunction after coronary artery bypass grafting

Abstract: Post-operative cognitive dysfunction (POCD) is a complication of the central nervous system characterized by mental disorders, anxiety, personality changes and impaired memory. POCD occurs frequently after coronary artery bypass grafting (CABG) and can severely affect quality of life for patients. To date, the development of POCD biomarkers remains a challenge. Alterations in the expression of non-coding RNAs from brain tissue and peripheral blood have been linked to POCD. The present study aimed to detect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
2
21
0
1
Order By: Relevance
“…It was hypothesized that a substance in the body that could gather several miRNAs regulated the same specific target gene, then the regulatory action on the specific target gene would be obviously increased. It was interesting that circRNAs, a novel type of non-coding RNAs [15], were perceived as a rare curiosity to having a central regulatory role in RNA metabolism, and accumulating evidences suggested that circRNAs could function as miRNA sponges (the ceRNA mechanism), therefore, circRNA could relieve the inhibitory effect of miRNA on its target gene and increase the expression of the target gene [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was hypothesized that a substance in the body that could gather several miRNAs regulated the same specific target gene, then the regulatory action on the specific target gene would be obviously increased. It was interesting that circRNAs, a novel type of non-coding RNAs [15], were perceived as a rare curiosity to having a central regulatory role in RNA metabolism, and accumulating evidences suggested that circRNAs could function as miRNA sponges (the ceRNA mechanism), therefore, circRNA could relieve the inhibitory effect of miRNA on its target gene and increase the expression of the target gene [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…As we analyzed in other study about circRNAs [12], novel therapies should include multiple genes and pathways due to the complex mechanisms of major depression disorder. Because many pathophysiological processes of stress-related depression were regulated by several miRNAs, therefore these miRNAs may be commom targets of antidepressant therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that circRNA is involved in the occurrence and development of neurological diseases ( Chen et al, 2016 ), and circRNA is expected to become a new biomarker for neurological diseases, but to our knowledge, there are currently no reports of circRNAs related to POCD. In our previous experiment ( Wang et al, 2019 ), circRNA expression in the plasma exosomes of POCD patients after coronary artery bypass grafting was screened by circRNA gene microarray analysis, and the relative level of circRNA-089763 was found to be significantly increased by qRT-PCR validation. Structural prediction analysis showed that circRNA-089763 could sponge 10 kinds of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that brain tissues can release exosomes, which can carry non-coding RNAs (ncRNAs, such as microRNAs, long stranded non-coding RNAs, and circRNAs) and enter the blood circulation through the blood–brain barrier. In our previous experiment, we found that there were abnormal levels of circRNA-089763 in plasma exosomes of POCD patients after cardiac surgery ( Wang et al, 2019 ). However, we found that it was difficult to collect and extract exosomes, and the level of total plasma (not only plasma exosomes) circRNA-089763 in non-cardiac POCD patients is still unknown.…”
Section: Introductionmentioning
confidence: 99%